Placenta-specific 8 limits IFNγ production by CD4 T cells in vitro and promotes establishment of influenza-specific CD8 T cells in vivo. - Chris D Slade; Katie L Reagin; Hari G Lakshmanan; Kimberly D Klonowski; Wendy T Watford (PLoS ONE)
During type 1 immune responses, CD4 T helper 1 (Th1) cells and CD8 T cells are activated via IL-12 and contribute to the elimination of intracellular pathogens through interferon gamma (IFNγ) production. In this study, we identified Placenta-specific 8 (Plac8) as a gene that is uniquely expressed in Th1 CD4 T cells relative to other CD4 T cell subsets and hypothesized that Plac8 may represent a novel therapeutic target in Th1 CD4 T cells. First, we determined that Plac8 mRNA in CD4 T cells was induced following IL-12 stimulation via an indirect route that required new protein synthesis. Upon evaluating the functional relevance of Plac8 expression in Th1 CD4 T cells, we discovered that Plac8 was important for suppressing IFNγ mRNA and protein production by CD4 T cells 24 hours after IL-12 stimulation, however Plac8 did not contribute to pathogenic CD4 T cell function during two models of intestinal inflammation. We also noted relatively high basal expression of Plac8 in CD8 T cells which could be further induced following IL-12 stimulation in CD8 T cells. Furthermore, Plac8 expression was important for establishing an optimal CD8 T cell response against influenza A virus via a T cell-intrinsic manner. Altogether, these results implicate Plac8 as a potential regulator of Th1 CD4 and CD8 T cell responses during Th1 T cell-driven inflammation.